CEI (Production Engineer, 1976)
Eosinophilic esophagitis (EoE) is a chronic allergic inflammatory condition characterized by eosinophilic infiltration of the esophagus and dysregulated T-cell responses. Proton pump inhibitors (PPIs) are a treatment option for patients with EoE, however, biomarkers for non-invasive monitoring of treatment response are lacking. In this study, we prospectively enrolled twenty patients with EoE who were treated with PPIs, of whom nineteen completed their treatment, and analyzed peripheral blood immune profiles using mass cytometry (CyTOF), comparing them with age- and sex-matched healthy controls. Histologically, fourteen of nineteen patients achieved histologic remission, whereas immunophenotyping was performed in 17 patients (12 responders and 5 non-responders) because two samples contained insufficient cell numbers. The patients were also evaluated using the EoE Histology Scoring System (EoE-HSS; stage and grade), endoscopic findings, and validated questionnaires. Unsupervised clustering identified key T-cell populations altered by treatment, including Th2 central memory CD4+ T cells and CD8+ terminal effector and naïve subsets. Successful PPI therapy was associated with expansion of FOXP3+ T cells and reduction in cytotoxic CD56+ CD8+ T cells, modulations not detected in non-responders. Notably, peripheral CD4+ T-cell counts correlated with histologic disease severity (EoE-HSS), whereas eosinophil counts did not. These findings highlight dynamic shifts in circulating T-cell phenotypes following PPI therapy and suggest that expansion of FOXP3+ T-cells and reduction of CD56+ CD8+ T cell populations may represent candidate treatment-associated immune signatures in EoE. However, given the exploratory nature of this high-dimensional immunophenotyping study and the limited sample size, these findings should be considered hypothesis-generating and require validation in larger independent cohorts.